Investigation of interference from canine anti‐mouse antibodies in hormone immunoassays. (18th July 2019) - Bergman, Daniel; Larsson, Anders; Hansson‐Hamlin, Helene; Ström Holst, Bodil
Abstract: Background: Canine anti‐mouse antibodies are a potential source of immunoassay interference, but erroneous immunoassay results are not always easily identifiable. Anti‐Müllerian hormone (AMH) is a marker for the presence of gonads in dogs, but elevated AMH concentrations in neutered dogs could also be caused by antibody interference. For other assays, a discrepant result obtained after antibody precipitation might indicate antibody interference. Objectives: We aimed to evaluate if canine anti‐mouse antibodies are a source of erroneous results in the AMH assay and if antibody precipitation with polyethylene glycol (PEG) is a useful tool for detecting antibody interference in a variety of immunoassays used in the veterinary clinical laboratory. Methods: Twenty‐nine positive and 25 negative samples for anti‐mouse antibodies were analyzed for AMH, canine total thyroxine (TT4 ), canine thyroid‐stimulating hormone (TSH) and progesterone before and after treatment with PEG. Results that differed by more than four SDs from the intra‐assay coefficients of variation were considered discrepant. Elevated AMH concentrations in neutered dogs with anti‐mouse antibodies and no visible gonads present were considered evidence of interference. Results: Evidence of antibody interference was found in two samples analyzed for AMH. The presence of anti‐mouse antibodies did not lead to a higher proportion of discrepant results after PEG treatment for any of the immunoassays. The overall incidence of discrepant results for healthy controls was very high (73%). Conclusions: Canine anti‐mouse antibodies are a source of erroneous AMH results. Antibody precipitation with PEG is not a useful tool for detecting interference caused by such antibodies.